Primary Iliopsoas Abscess in an Infant: A Case Report - Chintakrinda, Ajay Kumar (J Indian Assoc Pediatr Surg, 2018)
Primary iliopsoas abscess (IPA) is rare in the infantile period. However, if treatment is not initiated soon, aggressive, and adequate, there is high risk for mortality or permanent damage to the hip joints. We present the case of a preterm neonate who presented at 2 months of age with swelling and restricted movements of the left leg for the past 1 week. A diagnosis of idiopathic left IPA was made due to Staphylococcus aureus which was drained surgically and treated with systemic antibiotics. Currently, the baby is 6 months old with no evidence of any sequelae.